Mother with child : transformations through childbirth - Rabuzzi, Kathryn Allen (Indiana University Press, 1994)
Rabuzzi, author of The Sacred and the Feminine and Motherself, contends that childbearing has been denigrated, denied, and devalued. This book is intended to help women rename, re-ritualize, reinterpret, and reframe childbearing for themselves and their partners.